Pengaruh Harga, Brand Image Dan Promosi Terhadap Keputusan Pembelian Virtual Item Game Online Mobile Legend (Studi kasus di komunitas Online Mobile Legend) - Febri Arisandi; Imam Yuwono (Prisani Cendekia, 2023)
The main objective of this research is to evaluate the influence of the Price (X1), Brand Image (X2), and Promotion (X3) variables on consumer behavior in making purchasing decisions for virtual items in the online game Mobile Legends. This research adopts a quantitative approach with a population consisting of members of the online Mobile Legends community, which is quite significant, with 108 respondents as the sample. Data is collected using a questionnaire with a Likert scale provided through Google Forms using the Snowball Sampling method.